Lincoln's christianity - Burkhimer, Michael, 1973- (Westholme Publishing, 2015)
Depicts the role of religion in Abraham Lincoln's presidency, particularly the role of extreme losses in his life and how the use of religious texts in his speeches and debates led to controversy throughout his presidency.